PENEGAKAN DIAGNOSIS DAN PENANGGULANGAN CERVICALYS HERNIATED NUCLEUS PULPOSUS - Bernadetha Nadeak (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This paper examines the exact and precise diagnosis of the Cervicalys Herniatted Nucleus Pulposus (CHNP). CHNP comes from the displacement of the nucleus pulposus in the intervertebral disc at the cervical level, which can cause direct compression of the spinal cord or nerve root suppression. The posisition of the body which is less ergonomic during daily activities as a result of a misposition in a long time so as to cause high levels of stress on the muscles and tissues supporting the body in the long run and asymmetrical loading on intradiscal (disc migration). This condition causes the transfer of the nucleus pulposus to the front of the burden received, if this lasts a long time it can cause protrusion of the disc backwards so that it can directly irritate pain-sensitive posterior longitudinal ligaments. The purpose of this study is to find out how the precise and exact diagnosis of CHNP is. The research method used is library research, by referring to books, journals, articles relating to topics discussed as data sources to answer research question. The results of this study is; there are several ways that can be done in CHNP diagnosing such as: a) laboratory examination; b) imaging; c) electrodiagnostic, d) somatosensory evoked potentials. While the prevention of CHNP can be done in several ways such as: a) physical therapy; b) cervical traction; c) pharmacology; d) surgery; e) prevention; f) biomechanics; g) pathophysiology, and; h) decreased structure of the intervertebral disc. It can be concluded that in the accurate and precise enforcement and handling of CHNP, it is recommended to do the several methods mentioned above. Keywords: cervicalys herniated nucleus pulposus, head and neck position